Mirabegron in the Management of Overactive Bladder Syndrome in Ghazi Al-Hariri Hospital - Hiba H. Razaq; Mohammed B. Ismail; Mohamed E. Abdelrhman (مجلة كلية الطب)
Background: An individual’s quality of life is adversely affected by overactive bladder (OAB) symptoms. The key element that characterizes OAB is urgency which together with nocturia and urge urinary incontinence, are considered the most irksome symptoms. The side effects of the anticholinergic medication have caused a significant number of patients to discontinue their treatment. More recently, there has been research conducted on the potential correlation between an anticholinergic burden and the development of dementia. The detrusor muscle has been demonstrated to relax as a result of the activation of β3 adrenoceptors, which in turn facilitated the development of the first β3 adrenoceptor agonist. Mirabegron is the initial medication in this category to receive approval for the treatment of an overactive bladder.